Predictive Factors of Physician Visits in Older People with Chronic Constipation - Abdul Wahab, Patimah; Mohd Yusoff, Dariah; Lee, Yeong Yeh; Abdul Kadir, Azidah; Ali, Siti Hawa (2021)
Objective: The aim of this study was to examine the predictive factors of physician visits in Malaysian older people with chronic constipation. Methods: A retrospective cohort study was conducted among 129 community-dwelling older people aged 60 years old and self-reported chronic constipation. The data were obtained from a multicenter health clinics survey that was conducted in a state of the northeast of Peninsular Malaysia between November 2016 and January 2017. The participants were stratified according to the physician visit to manage chronic constipation (yes or no) within the past 12 months. The binary logistic regression analysis was used to identify the predictive factors of the physician visit. Results: A total of 11% (N = 14) older people had visited the physicians to manage their chronic constipation. The employed or retired older people (OR = 5.14, 95% CI = 1.29 - 20.48, p = 0.02), having between moderate and high physical activity (OR = 12.85, 95% CI = 1.30 - 127.10, p = 0.029), and presence of abdominal bloating (OR =7.7, 95% CI = 1.97 - 30.06, p = 0.003) and Bristol stool forms of type 1 and 2 (OR =4.59, 95% CI = 1.11 - 18.97, p = 0.035) predicted the physician visit in older people with chronic constipation. Conclusion: Older people who were financially independent, kept an active life, and presented with symptoms of abdominal bloating and hard stool, tended to visit the physician to manage chronic constipation. Clinically, monitoring satisfaction with chronic constipation management following a visit to the physician could be beneficial.